Cassava derivatives in ice cream formulations: effects on physicochemical, physical and sensory properties - de Souza Fernandes, Daiana [UNESP]; Leonel, Magali [UNESP]; Del Bem, Marilia Sbragia [UNESP]; Mischan, Martha Maria [UNESP]; Garcia, Émerson Loli [UNESP]; dos Santos, Thaís Paes Rodrigues [UNESP] (Springer Nature, 2017)
In the present study, the effects of derivatives of cassava, maltodextrin and bagasse, on the physicochemical, physical and sensory properties of ice creams were investigated. The content of cassava maltodextrin increased significantly the content of carbohydrate and total soluble solids and decreased lipids content. The effect of cassava bagasse was more pronounced than the maltodextrin on physical and sensory parameters. Increased percentage of cassava bagasse in formulation led to decrease of overrun, melting and luminosity, but increased hardness and unfreezable water. Sensory attributes were mainly influenced by cassava bagasse inclusion. The results suggested the potential use of cassava derivatives in ice cream formulations. Ice creams with low percentage of cassava bagasse (1.5) and intermediate values of cassava maltodextrin (3.65%) had good nutritional, technological and sensorial acceptance.
Keywords: Composition; Fat substitute; Fiber; Maltodextrin; Texture; Thermal properties